2015
DOI: 10.2139/ssrn.2707536
|View full text |Cite
|
Sign up to set email alerts
|

Interrelation between Growth and Inequality

Abstract: on ongoing and recently completed research and policy studies undertaken by the Asian Development Bank (ADB) staff, consultants, or resource persons. The series deals with key economic and development problems, particularly those facing the Asia and Pacific region; as well as conceptual, analytical, or methodological issues relating to project/program economic analysis, and statistical data and measurement. The series aims to enhance the knowledge on Asia's development and policy challenges; strengthen analyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…However, positive and significant results are obtained when they are used in the form of interaction terms with institutions, confirming the fact that institutions enhance the working of fiscal policy. Institutions have positive and significant effect on economic growth as strong institutions secure fiscal system and motivate investors to invest within a country (Hassan, 2002; Kemal, 2003; Kang, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, positive and significant results are obtained when they are used in the form of interaction terms with institutions, confirming the fact that institutions enhance the working of fiscal policy. Institutions have positive and significant effect on economic growth as strong institutions secure fiscal system and motivate investors to invest within a country (Hassan, 2002; Kemal, 2003; Kang, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Institutions have a positive and significant impact on inclusive growth. Institutions can significantly enhance the growth by supervising the activities of government and by ensuring a proper use of resources (Kang, 2015; Heshmati et al , 2014). Government expenditure has positive and statistically significant effects on inclusive growth but taxes have negative and insignificant impact on inclusive growth.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The result was that economic growth negatively affected poverty but positively influenced the income disparity. Meanwhile, Kang (2015) found that economic growth correlated negatively toward income disparity. Similar results were obtained by with research of Latin American countries that showed that economic growth negatively affected the income disparity.…”
Section: Literature Reviewmentioning
confidence: 99%